Legal Certainty and Justice in Providing Pro Bono Services by Notaries for the Indigent - Ni Putu Radha Pradina Putri; I Nyoman Bagiastra (Warmadewa Press, 2026)
This study aims to examine the ambiguity of the norms in Article 37 of the Notary Law regarding the obligation to provide free notary services to people who are unable to pay, particularly regarding the criteria for recipients and the form and limitations of the legal services that must be provided. The research uses a normative legal research method with a regulatory approach, a conceptual approach, and an analytical approach, as well as a technique for collecting legal materials through the snowball method. The results of the study show that the provisions of Article 37 paragraph (1) of the UUJN still contain vague and ambiguous norms, which are further reinforced by the 2025 Notary Code of Ethics amendment that no longer explicitly regulates the provision of services without honorarium, thus causing inconsistency between ethical norms and positive law as well as the absence of operational implementing regulations. This condition causes inconsistent implementation of obligations and has the potential to cause legal uncertainty and injustice. Normatively, the form of free services includes legal consultation, counseling, and exemption from fees, while still taking into account administrative costs outside of notary services. Therefore, clear criteria for recipients, operational technical regulations, and synergy between professional organizations, government agencies, and other stakeholders are needed to realize the effective, fair, and sustainable implementation of free legal services.